ANALYSIS OF PRODUCT DEVELOPMENT STRATEGY AND POSITION BY USING MATRIC BCG AND PLC (Case Study Mr. Hari’s Chicken Egg Business in Bengkulu City) - Afriani, Sulisti; Yanti, Rina Trisna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
A business established generally aims to obtain maximum profit, one of which is by using increasing the volume of sales made. If this became a goal, then how to maintain the business is needed so that its surviral can be maintained and developed. In this study, Mr. Hari’s chicken egg business is one example of a business that require a strategy in developing its business and needs to know the position of the products it sells. The analytical tools in this research are BCG (Boston Consulting Group) Matrix and PLC (Product Life cyle). From the results of research with BCG analysis, it can be seen that the growth rate of the Mr. Hari’s chicken egg business market in 2020 is 27 % and the relative market share is 1.5x. This shows that the market growth rate and relative market share have a high value. It can be seen that Mr. Hari’s chicken egg business is in the “Stars Category”, the business unit is at a high growth rate, with a high share. This condition illustrates the great potential for a business until to be developed in the long term. In relation to the Product Life Cycle (PLC), it can be seen that position og Mr. Hari’s chicken egg business is at “The Growth Stage”, where at this stage it can expand the marketing network, so the stategy used is to maintain (hold), the product still in the same category. Keywords: Strategy, BCG (Boston Consulting Group), PLC (Product Life Cyle)